The relationship between atypical antipsychotics drugs, QT interval prolongation, and torsades de pointes: implications for clinical use. Issue 5 (3rd May 2020) - Ruiz Diaz, Juan Carlos; Frenkel, Daniel; Aronow, Wilbert S.
ABSTRACT: Introduction : Increased mortality has been observed in patients with mental health disorders. Specifically, exposure to antipsychotic medications conveys a greater than 2 fold risk of sudden death, thought to be mediated through effects on QT prolongation and risk of torsades de pointes. Areas covered : We review the association between antipsychotic drugs and sudden cardiac death, the physiologic basis for these associations, assessment of patients at risk, and strategies to minimize risk of sudden cardiac death. Expert opinion : Despite the prevalence of antipsychotic medication use for many decades, there remain considerable challenges in reducing the associated risk of sudden cardiac death. A structured algorithm that incorporates patient clinical factors and antipsychotic drug factors may improve risk assessment and reduce the risk of adverse cardiac events. Future advancements in genetics and artificial intelligence may allow for enhanced risk stratification and predicting response (efficacy and adverse effects) to therapy.